PARTISIPASI DAN MANAJEMEN LEMBAGA PENDIDIKAN ISLAM OLEH MASYARAKAT PADA YAYASAN ISLAM BAHRUL ULUM BLAWI KARANGBINANGUN LAMONGAN : id - Muttaqin Choiri; Ni’matus Sholihah (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2021)
This research is basically a study carried out in order to map community participation in the management of Islamic education institutions, in this case as implemented by the Yayasan Islam Bahrul Ulum Blawi Karangbinangun Lamongan, the selection of this location is based on the initial assumption that the institution implements the community plays an active role in the development of Islamic Education institutions. The study in this study relates to: (1) The pattern of community participation in the development of Islamic educational institutions at the Yayasan Islam Bahrul Ulum Blawi Karangbinangun Lamongan? (2) What is the level of success of the model pattern of community participation in the development of Islamic educational institutions at the Yayasan Islam Bahrul Ulum Blawi Karangbinangun Lamongan? The method used is field research, with qualitative research research that aims to gain an understanding of social reality through inductive thinking processes related to the involvement of researchers in the situations and phenomena under study, the data needed is the field and literature. The data collection method uses Triangulation data with observation, interviews, questionnaires and document studies. The Result of this reseach, Management developed by the Yayasan Islam Bahrul Ulum is participatory management with an open management system, through several things, including deliberation, joint work, and mutual support between the foundation as the manager, and the community in general as charity investors and jariyah, in this case the community is also a supervisor on the management system of Islamic education institutions. By involving the community participation in this model, the community indirectly feels that they have ownership and share in the development of Islamic education programs, so that school management or foundations feel they have a responsibility to the community, both material and non-material.